Enhancing EFL Students' Reading Comprehension through SQ3R Technique: A Pre-Experimental Study - Ratni Ratni; St. Hartina; Magfirah Thayyib; Husnaini Husnaini (FOSTER: Journal of English Language Teaching, 2025)
This study aims to analyze the effectiveness of Survey, Question, Read, Recite, and Review (SQ3R) technique in improving students' reading comprehension at SMPN 7 Palopo. The study employed a quantitative approach with an experimental design, involving students as research participants. The researcher used a total sampling which consists of 30 students. The researcher used reading tests as instruments in this study. The results showed that the average score of students in the post-test was higher than the average score obtained by students in pre-test (33.83<68.27). Apart from that, the t0 (ttest) value is 22.261 with a df (degrees of freedom) value of 29, while the tt (ttable) value is 2.042 for a standard significance level of 0.05 at df = 30. It shows that the value of the t-test is higher that the value of the t-table. The researcher also found a value (p) of 0.00 and alpha (α) of 0.05, resulting in p<α (0.00<0.05). The results revealed that the SQ3R technique significantly improved students' reading comprehension compared to conventional methods. Students taught using this technique demonstrated better abilities in identifying main ideas, specific information, and drawing conclusions from texts.